If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2f = 3f + 7 Reorder the terms: 2f = 7 + 3f Solving 2f = 7 + 3f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-3f' to each side of the equation. 2f + -3f = 7 + 3f + -3f Combine like terms: 2f + -3f = -1f -1f = 7 + 3f + -3f Combine like terms: 3f + -3f = 0 -1f = 7 + 0 -1f = 7 Divide each side by '-1'. f = -7 Simplifying f = -7
| 22=9x+2-4x | | -3(1+8x)=-171 | | y=2/3(13)+4 | | 17x+80=90 | | Z/4+1=6-z/4 | | 9(t-7)-2(t-5)=10 | | -8b+2b=-7b+6 | | -16-(-t)=-23 | | 9x+7.38=3x+15 | | -7=x/-14-1 | | 8n+72=3n-36 | | x+3x-3+2x^2+8x-5= | | 12xx=4(x+5) | | 375=500+t | | 28x-105=175 | | (0.12a+0.24)/3=0.114 | | 9x+16x-9=5(5x+10) | | 2n+8/n+4 | | b-1+6b=23 | | 0.99n+48y=c | | 31x+17y=364 | | 10x+24=114 | | -4x-15=12x-7 | | 4x+7-3x=9 | | 21x+20Y=570 | | 7(x+1)+4(2x-7)=6(2x+5) | | 60+(x+20)3x=180 | | 3.69/10=12c | | 18x-21=177 | | 2x+6=3(x-2) | | 4/5x+2=-1/5x+5 | | 7x+18x-9=5(5x+5) |